Selanikli Humour in Montreal: the Repertoire of Bouena Sarfatty Garfinkle (1916-1977) - Cohen, Judith R. (Judeo Espaniol: Textos satíricos judeoespañoles: de salonicenses o sobre salonicenses/Satirical Texts in Judeo-Spanish by and about the Jews of Thessaloniki, 2011)

National Affection: Céline Dion - Hurley, Erin (National Performance: Representing Quebec from Expo 67 to Celine Dion, 2011)
In National Performance, Erin Hurley examines the complex relationship between performance and national identity. How do theatrical performances represent the nation in which they were created? How is Quebecois performance used to define Quebec as a nation and to cultivate a sense of 'Quebec-ness' for audiences both within and outside the province? In exploring Expo 67, the critical response to Michel Tremblay's Les Belles Soeurs, Carbone 14's image-theatre, Marco Micone's writing practices, Cľine Dion's popular music, and feminist performance of the 1970s and 80s, Hurley reveals the ways in which certain performances come to be understood as 'national' while others are relegated to sub-national or outsider status. Each chapter focuses on a particular historical moment in Quebec's modern history and a genre of performance emblematic of the moment, and uses these to elaborate the nature of the national performances. Winner of the Northeast Modern Language Association's Book Prize, National Performance is sophisticated yet accessible, seeking to enlarge the parameters of what counts as 'Quebecois' performance, while providing a thorough introduction to changing discourses of nation-ness in Quebec

Kanadisches Französisch im Unterricht - Lynda Lemay: Les maudits Français [Le français canadien en classe - Lynda Lemay : « Les maudits Français »] - Thiele, Sylvia (Varietäten im Französischunterricht. 1. Französische Fachdidaktiktagung [Les variétés dans l'enseignement du français. 1er colloque de didactique du français], 2011)